Is a Positive Femoroacetabular Impingement Test a Common Finding in Healthy Young Adults? - Laborie, Lene B. (Springer-Verlag, 2013)
BACKGROUND: Femoroacetabular impingement (FAI) is an incompletely understood clinical concept that implies pathomechanical changes in the hip as a cause for hip-related pain in young adults. While a positive anterior impingement test is suggestive of FAI, its association with clinical and radiographic findings remain unconfirmed in healthy young adults. QUESTIONS/PURPOSES: We determined the prevalence of a positive test in 1170 young adults and examined its possible associations with (1) self-reported hip discomfort for the past 3 months; (2) weekly physical exercise; (3) hip ROM; and (4) radiographic findings associated with femoroacetabular impingement. METHODS: We invited 2344 healthy 19-year-olds to a population-based hip study between 2008 and 2009; 1170 patients (50%) consented. The study included questionnaires on medical and functional status, a clinical hip examination including the impingement test and hip ROM, and two pelvic radiographs (AP and frog-leg views). RESULTS: Based on at least one affected hip, 35 of 480 (7.3%) men and 32 of 672 (4.8%) women had positive impingement tests. Eighteen of the 1170 patients were excluded owing to suboptimal or missing radiographs. Self-reported hip discomfort in the women and increased physical exercise in the men were strongly associated with the positive impingement tests. Decreased abduction and internal rotation in the men, decreased flexion in both genders, and radiographic cam type findings in the men also were associated with positive tests. CONCLUSION: A positive test for anterior impingement is not uncommon in healthy young adults, especially in males. We believe it always should be performed along with pelvic radiographs in young, active patients presenting with hip pain. LEVEL OF EVIDENCE: Level II, diagnostic study. See the Guidelines for Authors for a complete description of level of evidence.